Ocena zasiedlenia sztucznych schronień przez popielicowate (Gliridae) w karpackich lasach - Fedyń, Izabela; Malak, Adela; Nowak, Katarzyna; Pierzchała, Ewa; Śnigórska, Katarzyna; Wąs, Joanna (Leśne Prace Badawcze, 2020)
Nest boxes for dormice (Gliridae) can significantly increase the habitat’s carrying capacity for these species in areas under high anthropopressure and facilitate the long-term monitoring of populations. As part of the active protection of dormice in the Carpathian Landscape Parks in Małopolska, in August and September 2019, 575 boxes of two different sizes were checked for the presence of adults, young or nests. Additionally, habitat conditions within a 25 m radius were recorded (e.g. forest stand, estimated understory cover, the approximate number of natural shelters, fruiting plant species). The vast majority of all nest boxes – 79% – were used by dormice, but also birds and insects frequently occupied these shelters. Out of four species of dormice that occur in Poland, two were recorded in the study area: hazel dormice Muscardinus avellanarius and fat dormice Glis glis . They were found in all surveyed landscape parks and inhabited mainly fir stands. Hazel dormice preferred smaller nest boxes and were generally more common than fat dormice, which preferred large boxes. On the other hand, fat dormice were more common in areas rich in fruiting plant species. Our research thus confirmed the usefulness of artificial shelters for dormouse in active protection.